Use of validation by enterprises for human resource and career development purposes - (:unkn) unknown (Publications Office of the European Union, 2014)
"European enterprises give high priority to assessing skills and competences, seeing this as crucial for recruitment and human resource management. Based on a survey of 400 enterprises, 20 in-depth case studies and interviews with human resource experts in 10 countries, this report analyses the main purposes of competence assessment, the standards and methods applied, the employee groups targeted and the way results are documented and used. The study shows that competence assessment practices predominantly target executives and technical specialists, to a lesser extent other employees. Company size influences the way assessments are carried out, the larger the company, the more formalised approaches are. Outcomes of assessments are mainly used for internal company purposes; at this stage, therefore, validation in enterprises supports those seeking alternative employment or further learning only to a limited extent." (Editor, BIBB-Doku)
Keywords: L 6.3.1 Diagnose- & Messinstrumente; L 8 Diagnostik / Eignung; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.2 Europa; Kompetenzbewertung; Kompetenzfeststellung; Kompetenzdiagnostik; Betrieb; Personalentwicklung; Europa